Viable mpox virus in the environment of a patient room - Kalisvar Marimuthu; Judith Chui Ching Wong; Poh Lian Lim; Sophie Octavia; Xiaowei Huan; Yi Kai Ng; Jun Jing Yang; Stephanie Sutjipto; Kyaw Zaw Linn; Yin Xiang Setoh; Chong Hui Clara Ong; Jane Griffiths; et al. (International Journal of Infectious Diseases, 2023)
We conducted a prospective environmental surveillance study to investigate the air, surface, dust, and water contamination of a room occupied by a patient infected with mpox virus (MPXV) at various stages of the illness. The patient tested positive for MPXV from a throat swab and skin lesions. Environmental sampling was conducted in a negative pressure room with 12 unidirectional high efficiency particulate air filter (HEPA) air changes per hour and daily cleaning of the surfaces. A total of 179 environmental samples were collected on days 7, 8, 13, and 21 of illness. Among the days of sampling, air, surface, and dust contamination showed the highest contamination rates on day 7 and 8 of illness, with a gradual decline to the lowest contamination level by day 21. Viable MPXV was isolated from surfaces and dust samples and no viable virus was isolated from the air and water samples.